The Effect of Absenteeism and Clinic Protocol on Health Outcomes : The Case of Mother-to-Child Transmission of HIV in Kenya - Goldstein, Markus; Graff Zivin, Joshua; Habyarimana, James; Pop-Eleches, Cristian; Thirumurthy, Harsha (American Economic Association, 2014)
We show that pregnant women whose first clinic visit coincides with the nurse's attendance are 58 percentage points more likely to test for HIV and 46 percent more likely to deliver in a hospital. Furthermore, women with high pretest expectations of being HIV positive, whose visit coincides with nurse attendance, are 25 and 7.4 percentage points more likely to deliver in a hospital and receive PMTCT medication, and 9 percentage points less likely to breast-feed than women whose visit coincides with nurse absence. The shortcomings that prevent pregnant women from testing on a subsequent visit are common in sub-Saharan Africa.